The role of long non-coding RNA FGD5-AS1 in cancer. Issue 4 (1st April 2022) - He, Na; Xiang, Linbiao; Chen, Lei; Tong, Haobin; Wang, Keshen; Zhao, Jie; Song, Feixue; Yang, Hanteng; Wei, Xinyuan; Jiao, Zuoyi
ABSTRACT: Long noncoding RNAs (lncRNAs) refers to a class of RNAs that have at least 200 nucleotides and do not encode proteins, and the relationship between lncRNA and cancer has recently attracted considerable research attention. The lncRNA FGD5-AS1 is a newly discovered lncRNA with a length of 3772 nucleotides. Studies have found that FGD5-AS1 is abnormally highly expressed in many cancer tissues and was closely related to the lymph node metastasis, tumor invasion, survival time, and recurrence rate of various cancers. Mechanistic analyses show that FGD5-AS1 can stabilize mRNA expression by sponging miRNA, which not only induces cancer cell proliferation, metastasis, invasion, and chemoresistance in vitro, but also promotes tumor growth and metastasis in vivo. In addition, FGD5-AS1 can serve as a diagnostic or prognostic marker for a variety of cancers. This review demonstrates the clinical significance of FGD5-AS1 in human cancer and its role in tumorigenesis and tumor progression. Graphical abstract: uf0001